Integrasi Kompetensi Lulusan Pendidikan Formal Dan Non Formal Berbasis Pesantren: Studi Kasus di Pondok Pesantren HM Al-Mahrusiyah Kediri - AB. Musyafa Fathoni; Kadi; A. Nu’man Hakim (JOM, 2022)
This study aims to analyze the background, formulation process, and implications of the policy integrating formal education graduation standards with madrasah diniyah at Pondok Pesantren HM Al-Mahrusiyah Kediri. In the context of pesantren that oversee formal educational institutions, challenges arise in determining graduate competency standards. On one hand, formal educational institutions have autonomous rights in setting graduation standards. On the other hand, pesantren uphold distinctive visions and missions that must be preserved, making the integration of both systems an inevitable necessity. This research employs policy theory with juridical, historical, and policy study approaches to understand how the integration of graduation standards is established and implemented. The findings indicate that the integration is driven by a shift in students' educational orientation within the pesantren and demands from both parents and the job market for graduates’ competencies. The policy formulation process involves deliberations between pesantren administrators, madrasah diniyah, and formal educational institutions, with pesantren serving as the primary institution determining graduation standards. Additionally, a juridical approach is adopted by involving parents in the policymaking process, ensuring broad support from all stakeholders. The implications of this policy are evident in the increased public trust in pesantren education quality. This integration also steers pesantren toward achieving dual competencies, encompassing both religious knowledge and professional skills. This concept, referred to as "Double Competence," affirms that pesantren graduates not only possess strong Islamic understanding but are also equipped to compete in the professional world.